Evaluation of an oral preventive protocol in children with acute lymphoblastic leukemia (Pesquisa Odontológica Brasileira, 2003)
This study was designed to assess the effectiveness of a preventive oral protocol in children receiving antineoplastic treatment for acute lymphoblastic leukemia (ALL) before initiating a larger intervention study. During a seven month period, fourteen children from two to ten years old with a diagnosis of ALL were evaluated. Patients with ALL who received a 0.12% chlorhexidine mouth rinse (seven children) were compared to a control group of patients who were not given the same preventive treatment (seven children) as to the occurrence of oral mucosal complications. Children in both groups received daily oral hygiene care, and were examined daily by the pediatric dentistry team until discharge. A significant decrease in the incidence of oral mucositis and ulceration was observed in the children who received a 0.12% chlorhexidine mouth rinse (p < 0.05 by Fisher's exact test). The findings obtained in the present trial are encouraging, and suggest that the systematic application of a preventive protocol reduces the incidence of oral complications in children with ALL receiving chemotherapy.